2015
DOI: 10.1177/0014402915615885
|View full text |Cite
|
Sign up to set email alerts
|

Using Content Acquisition Podcasts to Improve Teacher Candidate Knowledge of Curriculum-Based Measurement

Abstract: Perhaps at no other time has teacher preparation been under such scrutiny and held to such high standards. To illustrate, teacher preparation programs are challenged to develop, adopt and consider efficient methods to train teacher candidates to understand and implement evidence-based practices for teaching and supporting students with exceptionalities (Maheady, Smith, & Jabot, 2014). The end goal is for teacher candidates to master a critical corpus of evidence-based practices that will be implemented with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 42 publications
5
58
1
Order By: Relevance
“…Results were compared to a contrast group who received the same content via a practitioner‐friendly text and found that participants who learned using the CAP scored significantly higher on knowledge and application measures. Participants in the CAP group also reported higher levels of motivation during instruction than participants in the text‐only group (Kennedy et al., ). The data from the literature cited above indicate that preservice special education teachers can develop positive beliefs about CBM and learn to use it effectively, yet the data are limited, and specific methods for studying and supporting preservice teachers’ learning and use of CBM have not been sufficiently examined.…”
Section: Curriculum‐based Measurementmentioning
confidence: 99%
“…Results were compared to a contrast group who received the same content via a practitioner‐friendly text and found that participants who learned using the CAP scored significantly higher on knowledge and application measures. Participants in the CAP group also reported higher levels of motivation during instruction than participants in the text‐only group (Kennedy et al., ). The data from the literature cited above indicate that preservice special education teachers can develop positive beliefs about CBM and learn to use it effectively, yet the data are limited, and specific methods for studying and supporting preservice teachers’ learning and use of CBM have not been sufficiently examined.…”
Section: Curriculum‐based Measurementmentioning
confidence: 99%
“…However, a number of intervention studies have provided nuance regarding how PSTs respond to instruction in how to use data and assessments including their abilities, perceptions, and selfefficacy (e.g., Kennedy et al, 2016;Reeves & Chiang, 2018). Computer-mediated platforms have shown promise in AL interventions as well (e.g., Alkharusi et al, 2010;Wang, Wang, & Huang, 2008;Zwick et al, 2008).…”
Section: Preservice Teacher Educationmentioning
confidence: 99%
“…For example, CAP-Ts are created to adhere to the coherence principle by only containing relevant content. For a detailed description of Mayer's instructional design principles as implemented within CAP-Ts see Kennedy, Wagner, et al, 2015 as well as Kennedy et al (2011).…”
Section: Content Acquisition Podcasts For Teachers (Cap-ts)mentioning
confidence: 99%